Role of glutamate receptors in tetrabrominated diphenyl ether (BDE-47) neurotoxicity in mouse cerebellar granule neurons. (22nd January 2016) - Costa, Lucio G.; Tagliaferri, Sara; Roqué, Pamela J.; Pellacani, Claudia
Highlights: Toxicity of BDE-47in cerebellar granule neurons is decreased by antagonists of ionotropic glutamate receptors. BDE-47 increases intracellular calcium and causes oxidative stress. These effects of BDE-47 appear to be secondary to an increase of extracellular glutamate. Abstract: The polybrominated diphenyl ether (PBDE) flame retardants are developmental neurotoxicants, as evidenced by numerous in vitro, animal and human studies. PBDEs can alter the homeostasis of thyroid hormone and directly interact with brain cells. Induction of oxidative stress, leading to DNA damage and apoptotic cell death is a prominent mechanism of PBDE neurotoxicity, though other mechanisms have also been suggested. In the present study we investigated the potential role played by glutamate receptors in the in vitro neurotoxicity of the tetrabromodiphenyl ether BDE-47, one of the most abundant PBDE congeners. Toxicity of BDE-47 in mouse cerebellar neurons was diminished by antagonists of glutamate ionotropic receptors, but not by antagonists of glutamate metabotropic receptors. Antagonists of NMDA and AMPA/Kainate receptors also inhibited BDE-47-induced oxidative stress and increases in intracellular calcium. The calcium chelator BAPTA-AM also inhibited BDE-47 cytotoxicity and oxidative stress. BDE-47 caused a rapid increase of extracellular glutamate levels, which was not antagonized by any of the compounds tested. The results suggest that BDE-47, by still unknown mechanisms, increases extracellular glutamate which in turn activates ionotropic glutamate receptors leading to increased calcium levels, oxidative stress, and ultimately cell death.